Prevention of Oral Health in Persons with Tobacco Smoking of Steam Cocktails - Elena Emelina (Journal of Global Pharma Technology, 2020)
Recently, tobacco smoking has an epidemiological character. The largest number of smokers, according to many studies, was found between the ages of 30 and 35. Studies conducted by the World Health Organization (WHO) indicated that if a young man smoked at least two cigarettes, 70 out of 100 would continue to smoke for life. Due to the increasing prevalence of tobacco smoking, WHO began to consider smoking not only as a bad habit, but also included tobacco dependence in the International Statistical Classification of Diseases and Health Problems (10th revision); Class V: Mental and behavioural disorders; group: Mental and substance use behavioural disorders; heading: Mental and behavioural disorders caused by tobacco use (code F 17). Keywords: Oral hygiene, Tobacco smoking, Hookah smoking, Health, Safety, Smoker.